2011
DOI: 10.1159/000328043
|View full text |Cite
|
Sign up to set email alerts
|

Does an Inflammatory Pattern at Primary Biopsy Suggest a Lower Risk for Prostate Cancer at Repeated Saturation Prostate Biopsy

Abstract: Introduction: To evaluate if an inflammatory pattern at primary biopsy is associated with a lower risk for cancer in men submitted to repeated saturation prostate biopsy (SPBx). Methods: From January 2005 to January 2010, 320 patients, after a negative primary extended biopsy (median 18 cores), underwent SPBx by transperineal approach performing 27 cores (median). 210 (65.6%) patients had a normal parenchyma and 110 had an inflammatory pattern (34.4%) at primary biopsy (none of them complained of symptoms sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Although the causes of prostate inflammation are to the best of our knowledge poorly understood, acute and chronic inflammatory infiltrates are frequently observed in prostate biopsies. Previous studies have indicated that between 35% to 100% of prostate biopsies performed for concern about PCa had some histological evidence of inflammation . The variability in prevalence is likely due to the fact that inflammation is not routinely evaluated or reported by pathologists.…”
Section: Discussionmentioning
confidence: 99%
“…Although the causes of prostate inflammation are to the best of our knowledge poorly understood, acute and chronic inflammatory infiltrates are frequently observed in prostate biopsies. Previous studies have indicated that between 35% to 100% of prostate biopsies performed for concern about PCa had some histological evidence of inflammation . The variability in prevalence is likely due to the fact that inflammation is not routinely evaluated or reported by pathologists.…”
Section: Discussionmentioning
confidence: 99%
“…An inflammatory pattern at primary biopsy is not associated with a decrease in prostate cancer incidence at repeated saturation prostate biopsy; therefore, only an accurate clinical evaluation including more parameters (i.e. urinary PCA3) could hopefully select men who need to undergo rebiopsy in the presence of persistent suspicion of cancer [15]. Evaluation of the preventive effect of finasteride on chronic bacterial prostatitis in Wistar rats suggest the possibility that finasteride has a preventive effect on development of chronic bacterial prostatitis, although there is as yet no consensus on the mechanism of this effect [16].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that between 35% and 100% of prostate biopsies done for suspected prostate cancer had some histologic evidence of inflammation (12)(13)(14)(15). However, factors associated with inflammatory changes in the prostate of men undergoing biopsy are largely unknown.…”
Section: Introductionmentioning
confidence: 99%